EFEKTIVITAS PERAN HUMAS DALAM MENJALIN KERJA SAMA DENGAN DUNIA USAHA DAN INDUSTRI DI MA MAMBA’UL KHOIRIYATIL ISLAMIYAH BANGSALSARI - Tarissa Rahmatul Indah Yani; Tyas Kurnia Sari; Wirdatul Jannah; Rofiq Hidayat (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2025)
This research was conducted at MA Mambaul Khoirotil Islamiyah Bangsalsari Jember because the institution actively collaborates with the business and industrial sectors to enhance the relevance of education to workforce needs. The study aims to describe the effectiveness of the public relations role in establishing cooperation with business and industrial partners at MA Mambaul Khoirotil Islamiyah Bangsalsari Jember. This research employs a qualitative approach with a field research design. Informants were selected purposively, including the principal, public relations staff, teachers, and industry partners. Data were collected through observation, interviews, and documentation, and analyzed descriptively to interpret field findings. The research findings show that the role of public relations at MA Mambaul Khoirotil Islamiyah Bangsalsari Jember is quite effective in building networks with DUDI, as evidenced by the increase in the number of partners from 1 to 3 and the implementation of several programs, such as internships, training, and guest lecturers, with a duration of 1–3 years. These data confirm that, despite the relatively simple public relations approach, the partnership remains productive and sustainable. This effectiveness is reflected in the increasing number of collaborations and the alignment between educational programs and industry needs.